Sowing Peace, Reaping Harmony: The Role of Religious Figures in Grounding Religious Moderation in Sulawesi (A Socio-Legal Study - B, M Taufan; Budiono, Arief; Ubay, Ubay; Marzuki, Marzuki; Sapruddin, Sapruddin; Hamiyuddin, Hamiyuddin; Hanafi, Muhammad Amin (Faculty of Law, Universitas Pekalongan, 2025)
This study critically inquires the role of religious figures within the framework of instilling the concept of religious moderation in Indonesia. The main reason for this study is that social facts in Indonesia today, indicate that there are certain people who interpret religion in extreme ways. This is the background behind the issuance of Presidential Regulation Number 18 of 2020 which places religious moderation as a fundamental social capital for nation building. In line with that, this paper maps out the strategies run by religious leaders in carrying out their roles in grounding the concept of religious moderation. This article is based on socio-legal research. The data were collected through observation, in-depth interviews, and documentation. The result of this study shows that religious leaders play an important role in instilling religious moderation by acting as inspirations in inter-religious interactions, motivators in understanding religious moderation, role models in moderation behavior, initiators of moderate religious perspectives, promoters of internal and external dialogue, mediators, catalysts, in carrying out Islam as rahmatan li al-alamin, and is at the forefront (spearhead) in socializing the concept of religious moderation.